INVENTARISASI ANGGREK ALAM DI HUTAN LINDUNG GUNUNG RAYA DESA TEMAJUK KECAMATAN PALOH KABUPATEN SAMBAS - Zed, Akhira Nurfansyah; Listiawati, Agustina; Rahmidiyani, Rahmidiyani (Jurnal Sains Pertanian Equator, 2020)
An inventory is needed to assess the biodiversity in a particular area. An inventory of orchid diversity is a data collection and recording in a place where there are orchid species in the area with varying species diversity. This study aims to discover the diversity of orchid species in the Gunung Raya Conservation forest in Temajuk Village, Paloh District, Sambas Regency. The method used is observation with a limit of 10% of the area of Gunung Raya Conservation Forest which is 120 ha,The data collection technique is completed by exploring Gunung Raya Conservation Forest by observing along the traversed path. This research was divided into three forest types, i.e. coastal forest, valley forest and hilly forest. Based on the results of orchid research found, there are 5 types in coastal forests, 15 types in valley forests and 34 types in hilly forests, a total of 19 genus orchids were found, namely Arides, Agrostophyllum, Anoectochilus, Appendicula, Bulbophyllum, Coelogyne, cymbidium, Dendrobium, dendrochilum, Oberonia, Eria, Flickingeria, Liparis, Luisia, Nephelaphyllis, Trichochogil, Podochil Trichotosia, and Vanda. The most frequent orchids found at the research location were Bulbophyllum orchids. Keywords : Inventory, Orchid, Temajuk Village, Protected Forest Gunung Raya